Shareholders’ Value of Saudi Commercial Banks: A Comparative Evaluation between Islamic and Conventional Banks using CAMEL Parameters - Saif-Alyousfi, Abdulazeez Y.H.; Saha, Asish; Md-Rus, Rohani (International Journal of Economics and Financial Issues, 2017)
Islamic banks are playing an important role in the financial sector in various economies, especially in Islamic nations. They provide most of the banking services as are provided by the conventional banks, albeit different in nomenclature and specific characteristics. So far, however, no econometric study has been reported in the literature which analyses and compares the contribution to shareholders’ value by Islamic and conventional banks. This paper uses pooled OLS and random effect model to investigate and compare the contribution to shareholders’ value by the Islamic and conventional banks in Saudi Arabia over the period 2000-2015. Our results indicate that Islamic banks in Saudi Arabia contribute more to the shareholders’ value than conventional banks. We find that higher capital ratio and credit risk lead to a decline in shareholders’ value of the conventional banks but this is not true in the case of the Islamic banks. We also find that higher level of loans decrease the conventional banks’ shareholders’ value but increase the same in the case of the Islamic banks. In contrast to Islamic banks, we find that conventional banks with higher liquidity have a lower shareholders’ value. Lastly, our results indicate that in general, shareholders’ value is associated negatively with declines in cost efficiency and bank size. Policy implications and possible strategic interventions have also been discussed.